CEO characteristics and frequency of share repurchases - Abdul Latif, Rohaida; Taufil Mohd, Kamarun Nisham; Kamardin, Hasnah (International Information Institute, 2016)
This study investigates whether companies repurchase shares to improve EPS and whether the characteristics of chief executive officer (CEO) play a significant role in the share repurchase frequency in Malaysian non financial companies. Based on robust profit regression using 274 observations of Malaysian actual share repurchase events between 2006 to 2010, we find significant evidence that companies frequently repurchase shares in an attempt to smooth reporting earnings.We also find that CEO duality, CEO expertise and CEO tenure can greatly influence the frequency of share repurchase events.The idea that managers utilize share repurchases to smooth earnings is quite worrying as it could potentially result in unfavorable implications for the company's long-run performance.